Historical masonry dwellings Maracaibo based Greywacke “eye stone” - Pineda, Susana; Bustamante, Rosa; Prendes, Nicanor; Sánchez, Isabel (Rev. Téc. Fac. Ing. Univ. Zulia, 2015)
Masonry materials of “eye stone” of homes in the historic center of Maracaibo replacement purposes and conservation are discussed. Petrophysical analysis methodology based on specimens exposed to determine the components and scalar properties by visual inspection; and X-ray diffraction, transmission optical microscopy, porosimetry and ultrasonic measurement and mechanical tests. The results show that the rock formation from “Miracle” is a ferruginous Greywacke, reddish, with abundant porosity (voids) of móldica, fenestral type, and intergranular noticeable to the naked eye and supports the popular name “eye stone”. It presents a low wicking; bulk density of 2889 kg / m3 and a low compression strength that is less than 5 MPa, decreasing considerably wet and conditioned by the loads oriented both parallel and perpendicular to the surface of stratification.